2020
DOI: 10.15244/pjoes/112205
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Assessment of Heavy Metals in Roadside Agricultural Soils

Abstract: Soil contamination of heavy metals is widespread, raising concerns about agricultural risks. We are investigating the concentrations and forms of the heavy metals lead, zinc, chromium, cobalt, nickel, cadmium and copper in agricultural soils near intensive traffic areas in two major cities in western Algeria: Tlemcen and Sidi Bel Abbes. We analyzed four soil samples cultivated with grapes (E1 and E2) and wheat (E3 and E4). The average concentrations of lead, cadmium, chromium and copper in these agricultural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…5 b, cadmium from traffic sources could easily be enriched by rice, rather than transformed into an activated state. Other research suggested that the cadmium from traffic sources could increase the content of carbonate Cd in soil, resulting in the decrease of Cd a proportion 53 . On the other side, leaf tissue also could increase the proportion of water-soluble Cd in plants 54 , indicating that cadmium in rice might not transfer from the soil directly.…”
Section: Resultsmentioning
confidence: 99%
“…5 b, cadmium from traffic sources could easily be enriched by rice, rather than transformed into an activated state. Other research suggested that the cadmium from traffic sources could increase the content of carbonate Cd in soil, resulting in the decrease of Cd a proportion 53 . On the other side, leaf tissue also could increase the proportion of water-soluble Cd in plants 54 , indicating that cadmium in rice might not transfer from the soil directly.…”
Section: Resultsmentioning
confidence: 99%
“…The level of soil contamination was assessed using geochemical index (I geo ). This index enables the assessment of heavy metal contamination by comparing current and pre-industrial metal content (Grzebisz et al 2002, Baran and Wieczorek 2015, Hanif et al 2016. The background values of Cd, Cu, Pb and Zn were taken from Kabata-Pendias and Pendias (2001) and amounted to 0.22, 6.5, 18 and 40 mg•kg -1 , respectively.…”
Section: Contamination Levels With Heavy Metalsmentioning
confidence: 99%
“…Contamination with heavy metals is among the greatest hazards to human health [1][2][3][4][5][6]. Mitchell et al [7] found that the main heavy metal contaminants in groundwater are As and Mn.…”
Section: Introductionmentioning
confidence: 99%